Assessment of utilization pattern of fixed dose drug combinations in primary, secondary and tertiary healthcare centers in Nepal: a cross-sectional study - Arjun Poudel; Mohamed Izham Mohamed Ibrahim; Pranaya Mishra; Subish Palaian (BMC, 2017)
Abstract Background Prescription practices, especially in South Asian countries, have come under investigation for quality. Although there have been no studies in Nepal that have analyzed the prescription pattern of FDCs for different levels of health care centers, several studies from Nepal and other countries in the region have revealed poor medicine use practices, including irrational use of fixed-dose drug combinations (FDCs). This research aimed at assessing the utilization pattern of FDCs among primary (PHC), secondary (SHC) and tertiary health care (THC) centers in Western region of Nepal. Methods A cross-sectional descriptive study was conducted at primary, secondary and tertiary health care centers in Western Nepal. One hundred prescriptions from each health care center were chosen through systematic random sampling. The International Network for Rational Use of Drug (INRUD) indicators were used to assess the rationality of prescribing. Both descriptive and inferential statistics were applied. The alpha level used was 0.05. Results At the PHC center, 206 medicines were prescribed, of which 20.0% were FDCs. Antimicrobials were the most prescribed FDCs (57.1%). The unit prices of all FDCs were below 100 Nepalese Price Rupees (NPRs). At the SHC center, 309 medicines were prescribed, and 30% were FDCs. Vitamins, minerals and dietary supplements were the most prescribed FDCs (25.8%). The costs of 63.5% of FDCs were below 100 NPRs. At the THC center, 33.5% of 270 medicines were FDCs. As at the SHC center, vitamins, minerals and dietary supplements were the most prescribed FDCs (40.6%). The costs of 50.5% of FDCs were below 100 NPRs. Conclusions FDCs were used extensively at different health care centers. The number of prescription in private centers, following established guidelines and the essential drug list (EDL), was much lower. The cost associated with the utilization of FDCs was higher in private sectors compared to public health care centers. In certain cases, the use of FDCs was questionable, and this study found a low use of essential medicines. Education to improve prescription practices at different healthcare levels is recommended.